Phân hủy 2,4,6-trinitrotoluen (TNT) trong chất thải rắn bằng sắt kim loại - Thảo, Phạm Mạnh (Vietnam Journal of Chemistry, 2014)
Contaminated solid waste at munition factories is a serious problem since it contains 2,4,6- trinitrotoluene (TNT), a nitroaromatic compound toxic to human health as well as to aquatic and terrestrial life. Our objective was to determine if zero-valent iron (Fe°) associated with H2O2 could be used to degrade 2,4,6- trinitrotoluene (TNT) in slurries of the solid waste and water. The results show that sequential treatments of a TNT-contaminated solid waste (277 mg TNT kg-1) with Fe° (1% w/w) within 6 hours followed by H2O2 (0.5% v/v) within 8 hours completely destroyed TNT and its highly toxic anilinic intermediates. The optimal performance of Fe0 powder was obtained when the reagent was added in four increments rather than in a single dose. Our observations also indicate that ion Cl- improved the performance of the reduction of TNT by Fe°.